2001
DOI: 10.1021/jf001307k
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Stability of the Major Almond Allergen in Foods

Abstract: Almond major protein (AMP or amandin), the primary storage protein in almonds, is the major allergen recognized by almond-allergic patients. A rabbit antibody-based inhibition ELISA assay for detecting and quantifying AMP in commercial foods has been developed, and this assay, in conjunction with Western blotting analyses, has been applied to the investigation of the antigenic stability of AMP to harsh food-processing conditions. The ELISA assay detects purified AMP at levels as low as 87 +/-16 ng/mL and can d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
79
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 17 publications
(20 reference statements)
12
79
0
Order By: Relevance
“…These antibodies, specific to almonds, retained partial cross-reactivity with some tree nuts (black walnut, hazelnut, brazil nut). A similar approach was used by Roux et al [10]for the detection of the almond major protein allergen in foods. In a study by Eigenmann et al [25], the specificity of IgE binding in peanut was analysed using a preliminary absorption to soybean proteins of cross-reacting antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These antibodies, specific to almonds, retained partial cross-reactivity with some tree nuts (black walnut, hazelnut, brazil nut). A similar approach was used by Roux et al [10]for the detection of the almond major protein allergen in foods. In a study by Eigenmann et al [25], the specificity of IgE binding in peanut was analysed using a preliminary absorption to soybean proteins of cross-reacting antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In one recent study, IgE-mediated allergy to almonds was found in 22% of symptomatic patients by means of positive skin prick tests and ImmunoCAP ® with IgE antibodies specific to almond [8]. Another recent report on the identification of almond allergens was based on a single case allergy [9], but only one major IgE-binding almond protein has been characterised as an allergen, namely almond major protein or amandin [10]. In this present work, two IgE-binding proteins isolated from almond seeds are reported and identified by sequence homology as 2S albumin and conglutin γ proteins.…”
Section: Introductionmentioning
confidence: 99%
“…As a tree nut allergen, it ranks third (15% reactive) behind walnut and cashew nut in the FAAN self reporting survey of tree nut allergies [45]and can be found in many foods. Despite these statistics and despite the fact that the proteins in almonds have been biochemically characterized [60, 61, 62, 63, 64, 65, 66, 67], relatively little has been reported regarding the identity of the allergens involved in almond sensitivity.…”
Section: Widely Consumed Tree Nutsmentioning
confidence: 99%
“…Nineteen other polypeptides were also resolved, however, these were of lesser quantitative importance as judged by staining by Coomassie Brilliant Blue. Probing of blotted amandin with human almond-allergic sera shows that the 42- to 44-kD bands are strongly reactive [60, 67]. Preliminary sequence data indicate that these peptides are from a protein in the legumin family [unpubl.…”
Section: Widely Consumed Tree Nutsmentioning
confidence: 99%
“…Several allergens have been described and some have been cloned. For most nuts ELISA methods have been described with high sensitivity and detection levels reaching as low as 0.2 mg/kg (Almond: Hlywka et al, 2000;Roux et al, 2001;Brazil nut: Clemente et al, 2004;Cashew nut: Wei et al, 2003;Hazelnut: Scheibe et al, 2001;Koppelman et al, 1999;Holzhauser and Vieths, 1999;Blais and Phillippe, 2001;Ben Rejeb et al, 2003;Stephan et al, 2002;Walnut: Niemann and Hefle, 2003). For specific nut allergen detection various ELISA test kits and DNA-based PCR and PCR-ELISA methods are commercially available .…”
Section: Nutsmentioning
confidence: 99%